Hydrodehalogenation of Polychloromethanes on Silver‐Based Gas Diffusion Electrodes. Issue 10 (26th May 2021) - Rondinini, Sandra; Pargoletti, Eleonora; Vertova, Alberto; Minguzzi, Alessandro
Abstract: This work reports the electroreduction of a volatile organic halide (trichloromethane) from an airborn stream. In the past years, we highlighted the role of polycrystalline silver as powerful electrocatalyst for the electroreductive hydrodehalogenation of volatile organic halides (VOH) in water/organic solvent mixtures, from 0 to 100 % of the aqueous component. The successful conversion of trichloromethane and 1, 1, 1‐trichloethane to the relevant dehalogenated compounds, methane and ethane have prompted us to extend the investigations to the treatment of gaseous effluents, adopting a silver Gas Diffusion Electrode (Ag‐GDE) and the appropriate cell design. In the field of electroreduction processes the possibility of using GDE to treat gaseous effluents for the removal of volatile organic pollutants represents an electrochemical challenge, and the treatment of N2 /CHCl3 gas mixtures fed into the cathodic Ag‐GDE compartment demonstrates the feasibility of the electroreductive detoxification process. Our results will be presented and discussed in terms of CHCl3 removal efficiency, selectivity and energy consumption in preparative electrolyses. Abstract : Cleaner air : This paper describes the possibility of using silver microparticles or nanoparticles, supported on a carbonaceous matrix, as suitable cathode to treat volatile organic halide in electroreduction processes. In this way, an airborne containing toxic volatile compound can be purified while producing a more valuable substance. The paper discusses the cathode behavior in terms of current efficiency, energy consumption, and formation of byproducts.